The COVID-19 Pandemic in Low-Income Countries with Different GHI Severities: A New Concept to Cope with COVID-19 in these Countries - Reuveni, Saada (Technium Social Sciences Journal, 2022)
This study focuses on low-income countries (LICs) with different GHI severities (low, moderate, and serious) with an interest in answering the following question: Are there any fundamental differences in the outcomes of countries with different GHI severities when dealing with the COVID-19 pandemic? This study considers four pandemic-related indicators, as well as three relationships among them. Statistical modeling and analysis were performed to examine the relationships between 95 LICs and four daily COVID-19 indicators. The countries were classified into three groups by GHI severity, and data were gathered from the Johns Hopkins Coronavirus Resource Center for January 2020 to August 2021 (i.e., before and after the first vaccines). The findings suggest: (i) a standardized set of interventions is unlikely to be applicable to all countries with different GHI severities; (ii) differences exist between the three groups in terms of their capacity to cope with the pandemic; and (iii) governments and policymakers in LICs should monitor and dynamically adjust their policies to accelerate their progression in strengthening their healthcare systems. This study introduces a new concept for coping with COVID-19 in LICs in a more effective way, one based on a country’s position on the GHI Severity Scale.